Variability of Gas Diffusion in Soils - Rose, Lewis Sam (2020)
Soil acts as a major transport pathway for various solids, liquids, and gases. Many processes observed across different scales, from gas exchange in the soil surrounding a single plant to landslides consuming hectares of forest, all begin with small changes in the subsurface and are affected by various external processes. Knowledge of gas movement in soils is critical for effective management and remediation. Gases in soil are often studied with the aim of elucidating other properties of the system. One property of interest is the effective soil gas diffusion coefficient, a value indicative of the rate at which a specific gas moves through a soil. The soil gas diffusion coefficient is often presented in relation to the rate of movement in free air. Determination of a specific diffusion coefficient is possible with a high degree of precision in laboratory studies, but the heterogeneity of natural soils (as well as the environmental conditions often present at field sites) make more “realistic” values difficult to obtain. The variability in undisturbed soils can be high both spatially and temporally. Soil gas is a complex mixture. The components of soil gas include the greenhouse gases carbon dioxide, methane, and nitrous oxide. Movements of such gases are of great interest when studying soil responses to climate and land use change. The major problem with attempting to model the movement of these gases is that they are all being created and destroyed at varying rates through the soil profile through biological and chemical interactions. This complexity easily conceals the underlying physical transport processes and makes determining physical characteristics very difficult. There are two main ways in which information can be obtained about soil gas movement: gas can be collected, and its properties measured, or information (often proxies) about soil gas composition can be measured in-situ. A useful tracer for soil gas movement is the ubiquitous radioisotope radon-222 (222Rn). The inert nature of radon-222 makes it an ideal soil gas tracer, and its negative health effects have been the driver of research into its detection and quantification in the environment. The radioactive decay of the nuclide radium-226 to radon-222 occurs at a constant rate with time and is a source of gas moving into the soil system at all points in space. Radioactive decay is a physical process unaffected by temperature, pressure, moisture content, biological or chemical conditions. Many literature methods have been devised to collect soil gas and to quantify radon activity concentrations in a gas sample. Laboratory and field studies often involve a large amount of invasive field work such as drilling soil cores or digging large soil pits. Field work takes energy and time, and risks fundamental change to the soil’s physical behaviour. Due to the heterogeneous nature of soils, data for one area does not necessarily apply to another. It does not make much sense to engage in a large field exercise only to produce data that is no longer applicable; a minimally invasive method of soil gas extraction is therefore attractive. As well as having a better chance that resulting data will represent the field site, minimally invasive methods can be employed on sensitive sites, including existing experimental plots, without causing undue damage or distress. Recent studies of radon gas, specifically, have displayed a move toward more intricate and expensive equipment for a more detailed analysis of the soil system. Whilst the science might not be disputable, the approach is not always appropriate: many areas of the world where radon is a major human health hazard, or where its use as a tracer may lead to a greater understanding of the local soil systems, require methods which are less expensive, easier to use, and more suited to remote or extreme environments than currently exist. The research reported in this thesis attempts to address this gap. In the studied soils, gas diffusion coefficients as resolved by the employed model varied by a factor of 2 over 12 months, and by a factor of 1.5 over 50 m. Over 18 months, soil gas radon concentrations themselves varied by a factor of 6 at a depth of 10 cm, and by a factor of 1.5 at a depth of 100 cm. The probe sampling method developed performed well in homogeneous, sandy soils; soil gas was easily extracted, and the depth concentration profile was closely approximated by diffusive theory in the form of Fick’s Second Law. The developed method of fitting soil gas diffusion coefficients to data was found to be sensitive to the gas production parameter. Clayey soils and soils with properties such as compaction or horizonation due to land slippage, were both more susceptible to error in gas sampling and produced depth concentration profiles that were not valid for fitting a single diffusion coefficient value.